2021
DOI: 10.1093/cercor/bhab208
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Inhibits Aging-Induced Telomere Attrition and Apoptosis in Astrocytes In Vivo and In Vitro

Abstract: Folic acid (FA) has been reported to inhibit astrocyte apoptosis and improve aging-induced disorders; however, its role in telomere attrition remains unclear. In present study, 4-month-old senescence-accelerated mouse prone 8 (SAMP8) mice were assigned to four treatment groups for the in vivo experiment: FA-deficient diet (FA-D) group, FA-normal diet (FA-N) group, low FA-supplemented diet (FA-L) group, and high FA-supplemented diet (FA-H) group. These mice were euthanized when 10 months old. There was also a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…16 In 1961, in the continuous culture of human diploid cells, the lifespan of fibroblasts was first found to be limited. 17 Thus far, a number of molecular mechanisms that regulate aging have been discovered, such as telomere dysfunction, 18 loss of proteostasis, 19 mitochondrial dysfunction, 20 stem cell exhaustion, 21 and epigenetic alterations. 22 The aging process is driven by a number of complex and important pathways, and many of those drivers are associated with chronic oxidative stress caused by elevated levels of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…16 In 1961, in the continuous culture of human diploid cells, the lifespan of fibroblasts was first found to be limited. 17 Thus far, a number of molecular mechanisms that regulate aging have been discovered, such as telomere dysfunction, 18 loss of proteostasis, 19 mitochondrial dysfunction, 20 stem cell exhaustion, 21 and epigenetic alterations. 22 The aging process is driven by a number of complex and important pathways, and many of those drivers are associated with chronic oxidative stress caused by elevated levels of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous in vitro studies found that folic acid supplementation decreased apoptosis in astrocytes via alleviating telomere attrition and telomere DNA oxidation damage [38,39]. However, other than astrocytes, the brain tissue is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that FA protected melanocytes from Hcy-induced apoptosis [ 14 ]. Interestingly, Li et al and Zhou et al observed that FA inhibited aging-induced apoptosis in astrocytes and neurocytes, respectively, suggesting that FA could suppress apoptosis in various conditions [ 15 , 24 ]. Additionally, our study showed the upregulation of Bax, the downregulation of Bcl2, and the inhibition of Caspase-3 activation in melanocytes undergoing oxidative stress following FA treatment, indicating that the antiapoptotic capacity of FA may result from decreasing cleaved Caspase-3 through modulating the ratio of Bax to Bcl-2 expression in oxidative injured melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the disruption of folate metabolism plays a role in the pathogenesis of vitiligo. Notably, some recent studies have found that FA possesses excellent antioxidant property and is effective in maintaining cellular redox status [ 15 , 16 ]. However, the effect of FA on melanocytes under oxidative stress in vitiligo has not been investigated before.…”
Section: Introductionmentioning
confidence: 99%